Challenges and Opportunities of India's Manufacturing Sector - Joumard, Isabelle (OECD Publishing, 2015)
The manufacturing sector has contributed little to income growth and its share in total merchandise exports has been declining. Manufacturing has not brought much new employment, and most of the recent rise in manufacturing employment has been in the informal sector, where workers are not covered by social security arrangements. Productivity of the manufacturing sector is low, partly because the relatively small size of manufacturing firms makes it difficult to exploit economies of scale. Despite abundant, low-skilled and relatively cheap labour, Indian manufacturing is surprisingly capital and skill intensive. Furthermore, firms have little incentive to grow, since by staying small they can avoid taxes and complex labour regulations. Land acquisition is slow, companies face frequent power outages and transport infrastructure is below par. This is especially harmful as manufacturing is highly reliant on well-functioning infrastructure. Stronger manufacturing would increase productivity and make growth more inclusive, while contributing to improved current account balance. In particular, India should aim for more formal jobs, as these tend to be the most secure and of highest productivity
Keywords: Economics; Industry and Services; India